2009
DOI: 10.1021/ic802271y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Atropisomerism of Fe(II) 2,6-Bis(N-arylimino)pyridine Complexes

Abstract: NMR spectra of free 2,6-bis(N-arylimino)pyridine (PDI) ligands displaying different substituents at the ortho and ortho' positions of the two N-aryl rings indicate that they can exist in syn (meso) and anti (chiral) configurations. These interconvert in solution at room temperature, via rotation of the aryl group. The corresponding paramagnetic FeX(2)(PDI) complexes exhibit the same kind of isomerism, a property that is thought to be important for their activity as alpha-olefin polymerization catalysts. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…14 In other cases, atropisomerism is not invoked, presumably since no experimental evidence exists to suggest its relevance. 15,17,19 Atropisomerism was implied by Small and Brookhart 20 and Ca ´mpora et al 21 for free asymmetric bis(imino)pyridine ligands and for select corresponding Fe(II) complexes; 13 C NMR spectroscopy provided evidence of hindered rotation about the imino N-aryl C bonds. It is notable that these authors do not invoke E/Z isomerization as an explanation for the fluxional behavior observed by NMR spectroscopy; presumably, the primary alkyl substituents on the imino carbon positions (methyl 20,21 or butyl 21 ) render the E,E-isomer energetically favorable.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…14 In other cases, atropisomerism is not invoked, presumably since no experimental evidence exists to suggest its relevance. 15,17,19 Atropisomerism was implied by Small and Brookhart 20 and Ca ´mpora et al 21 for free asymmetric bis(imino)pyridine ligands and for select corresponding Fe(II) complexes; 13 C NMR spectroscopy provided evidence of hindered rotation about the imino N-aryl C bonds. It is notable that these authors do not invoke E/Z isomerization as an explanation for the fluxional behavior observed by NMR spectroscopy; presumably, the primary alkyl substituents on the imino carbon positions (methyl 20,21 or butyl 21 ) render the E,E-isomer energetically favorable.…”
Section: Introductionmentioning
confidence: 93%
“…15,17,19 Atropisomerism was implied by Small and Brookhart 20 and Ca ´mpora et al 21 for free asymmetric bis(imino)pyridine ligands and for select corresponding Fe(II) complexes; 13 C NMR spectroscopy provided evidence of hindered rotation about the imino N-aryl C bonds. It is notable that these authors do not invoke E/Z isomerization as an explanation for the fluxional behavior observed by NMR spectroscopy; presumably, the primary alkyl substituents on the imino carbon positions (methyl 20,21 or butyl 21 ) render the E,E-isomer energetically favorable. This is in contrast to studies by Orrell et al where a symmetric bis(imino)pyridine ligand serves a bidentate ligand for Pd(II) or Pt(II), 22 Re(I) 23,24 and Pt(IV), 25 and E/Z isomerization of the non-coordinated imine arm is invoked in combination with atropisomerism (again, with methyl substituents on the imino carbon positions).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Accordingly, we describe herein the synthesis and characterization of bis(imino)pyridine complexes of iron(II) and iron(III). The bis(imino)pyridine ligand class is known 37 and has previously been employed in the synthesis of iron complexes. 38 Iron complexes of bis(imino)pyridines are widely utilized as ethylene polymerization catalysts, 39 and also have been used to catalyze cyclization or cycloisomerization reactions; 40 however, they have not been employed in the Mukaiyama aldol reaction to date.…”
Section: Scheme 1 the Mukaiyama Aldol Reactionmentioning
confidence: 99%
“…This approach offers the possibility of interconversion between atropisomers, which may be induced chemically, thermally, photochemically or electrochemically. 8 Currently, there are very few examples of this type; these involve diimine 9 or bisiminopyridine 10,11 ligands with di-orthosubstituted phenyl substituents on the imine N atom and some metal oligomers of 3-pyridyl porphyrin. 12 In all these cases the presence of two rotational axes leads to syn and anti isomers.…”
mentioning
confidence: 99%